STRATEGIC INFORMATION SYSTEMS PLANNING AND INFORMATION TECHNOLOGY FOR SCHOOL - Agus Susilo Nugroho (Widyagogik, 2020)
As a foundation, At-Thoat school has a routine agenda every year, namely the Admission of New Students (ANS). Even though they have implemented by online, they have not been able to realize one day service. The speed and automation of ANS services greatly helps the acquisition of new students. Because competition for new students is competitive. In addition, the number of new students at At-Thoat has also greatly influenced the survival of the school. The solution offered in this study for this problem is to compile a strategic design for Information Systems (IS) and Information Technology (IT) using the Ward and Peppard method, which are design methods capable of producing IS / IT strategies that are in line with business strategies. The first stage in applying this method in this research is the analysis of current conditions, both the organization as a whole and the IS / IT aspect. The next stage is an analysis of IS / IT needs in the future. The final stage is the preparation of IS / IT strategic steps. To analyze each of these stages, analysis tools are needed, namely: SWOT, critical success factor. The implementation of the Ward and Peppard methods and their analytical tools were able to identify and recommend IS / IT needs at At-Thoat School for the next 5 years. However, the resulting recommendations must be adjusted to the priority scale, because of the various limitations faced.